Religion and mental health among Nepal earthquake survivors in temporary tent villages - Jang, Mikyung (Mental health, religion & culture, 2018)
The aim of this study was to explore the relationship between mental health and the perceived importance of religion and the frequency of prayer among 200 children ages 10-18 years who lived in temporary camps for earthquake survivors in Nepal. The participants were examined using the Child Behavior Checklist (CBCL) 6-18 and were asked about the importance of religion in their lives. In contrast to expectation that high perceived importance of religion and prayer frequency have positive impacts on mental health after earthquakes, the results indicated significantly higher levels of withdrawal/depression. The group that prayed less frequently after the earthquakes had significantly higher scores for somatic symptoms, withdrawal/depression, anxiety/depression, social immaturity, internalising problems, and total CBCL scores. However, the clinical risk group (T score of 65 or higher in the CBCL total score), no significant difference according to the importance of religion showed and frequency of daily prayer.